Population status and threats to fishing cat Prionailurus viverrinus (Bennett, 1833) in Koshi Tappu Wildlife Reserve, Eastern Nepal - Mishra, Rama; Gautam, Birendra; Kaspal, Prativa; Shah, Shyam Kumar (Nepalese Journal of Zoology, 2021)
Koshi Tappu Wildlife Reserve (KTWR) in eastern Terai of Nepal is believed to hold a relatively healthy population of vulnerable fishing cats but has remained unexplored. We conducted camera trapping and questionnaire survey in KTWR and its buffer zone in the winter of 2016 and 2017 to estimate the population status and threats to fishing cat Prionailurus viverrinus. Camera trapping was conducted in 2016 on fish farms in the eastern buffer zone where we found a minimum of nine fishing cat individuals visiting the surveyed fish ponds. The frequency of their visits to fish ponds varied 0–5 (average 2) nights during seven active camera trap nights. A survey in the second year (2017) covered the entire reserve. Spatially Explicit Capture-Recapture models estimated a population of 20 fishing cats with density of 8.4/100 km2 in KTWR and the eastern buffer zone. We interviewed 50 fish farmers to understand the people’s perceptions towards fishing cats. More than 40% of the respondents reported fishing cats consuming fish from their farm. Retaliation and road kills were documented as major threats of fishing cats in the study area. The population of the fishing cat is found dependent partially on fish ponds, indicating the possibility of conflict with fish farmers. We recommend the detailed study on the movement of fishing cats between the reserve and fish farming area in the buffer zone.